Do motorisation statistics reflect the real geography of car ownership in Poland? - Kołsut, Bartłomiej; Stryjakiewicz, Tadeusz; Gadziński, Jędrzej (Quaestiones Geographicae, 2022)
The article aims to identify the shortcomings of the statistics describing the size and structure of passenger car parc in Poland, and to formulate the consequences of these limitations for geographical research. Analysed in detail, the shortcomings are divided into three groups: (1) ‘dead souls’, i.e. an overestimation of the number of vehicles which have not been on the road for a long time but remain on the register; (2) ‘cars with a grid’ (cars registered as trucks in which the cargo part is separated from passenger seats by a metal grid), i.e. an underestimation of the number of passenger cars and overestimation of the number of trucks related to the mass phenomenon of registering passenger cars as large goods vehicles (LGV-approved cars); and (3) company cars, i.e. an overestimation of the number of vehicles in cities where leasing companies and large enterprises owning those cars have their headquarters. The article determines the scale of car ownership overestimation in Poland and the areas where this overestimation is the highest, using districts (PL: powiaty) as basic spatial units. We conclude that the present motorisation statistics do not fully re flect the real geography of car ownership in Poland.